Dynamics of socially oriented non-profit organizations development as providers of socially important services in the regions of the Northwestern Federal District of the Russian Federation - A. S. Artamonova (Вестник университета)
The article analyzes the dynamics of socially oriented non-profit organizations (hereinafter – SONPOs) development in the context of their role in the social service system transformation. The study is based on the data of departmental statistics for 2018–2022 for the Northwestern Federal District regions using the comparative analysis methods. The analysis revealed that in all selected federal subjects the benchmarks for the non-state providers share in the total number of social service providers have been achieved. Among them, the SONPOs share ranges from 13 to 86 %. The assessment of the SONPOs development rates for all types of socially important services contained in the official statistical information has shown that, while their number is practically unchanged, the increase in the financial support volume leads to an increase in their consumers’ number. The most noticeable expansion of the target audience is observed in the field of culture and cinematography, but in general, there is a noticeable differentiation of regions in terms of the increase rate in the socially important services volume in various spheres. The identified discrepancies in various departmental registers of SONPOs are related to their inability to adapt to new conditions and may indicate the failure to overcome barriers that prevent these organizations from participating in providing social services commissioned by the state.